2013
DOI: 10.1098/rsif.2013.0720
|View full text |Cite
|
Sign up to set email alerts
|

Effective viscosity of puller-like microswimmers: a renormalization approach

Abstract: Effective viscosity (EV) of suspensions of puller-like microswimmers ( pullers), for example Chlamydamonas algae, is difficult to measure or simulate for all swimmer concentrations. Although there are good reasons to expect that the EV of pullers is similar to that of passive suspensions, analytical determination of the passive EV for all concentrations remains unsatisfactory. At the same time, the EV of bacterial suspensions is closely linked to collective motion in these systems and is biologically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…For example, it was suggested that pushers become hydrodynamically attracted to boundary surfaces by an inward flow perpendicular to the axis of net swimming [1]. Swimmer type further determines active rheological responses such as shear thinning in dense suspensions of microswimmers [14,15].…”
mentioning
confidence: 99%
“…For example, it was suggested that pushers become hydrodynamically attracted to boundary surfaces by an inward flow perpendicular to the axis of net swimming [1]. Swimmer type further determines active rheological responses such as shear thinning in dense suspensions of microswimmers [14,15].…”
mentioning
confidence: 99%
“…The active stress tensor σ represents the forcing of the fluid by the swimmers [8,16,17]. For dense suspensions, the bulk viscosity μ contains contributions from the solvent as well as passive and active contributions from the microswimmers [23][24][25][26][27][28]. For simplicity, we assume that the passive contribution is approximately given by the Batchelor-Einstein relation for spherical colloids, μ = μ 0 (1 + k 1 φ + k 3 φ 2 ), where μ 0 is the "bare" solvent viscosity, φ is the volume fraction, and k i are positive constants [23,[29][30][31].…”
mentioning
confidence: 99%
“…With or without such addition, the value of the critical index is of the order of 2. The higher order coefficients c i appear to be redundant as long as one is concerned with the correct estimates for the critical index S [51].…”
Section: Effective Viscosity Of Passive Suspensionsmentioning
confidence: 99%